2019
DOI: 10.1037/spq0000337
|View full text |Cite
|
Sign up to set email alerts
|

Universal screening in middle and high schools: Who falls through the cracks?

Abstract: Navigating academic demands in middle and high school may be particularly challenging for youth experiencing emotional and behavioral difficulties, and screening practices are a necessary first step in identifying youth in need of services. The goal of this study was to inform efficient universal screening practices in secondary schools by comparing 3 common methods of screening, including self-and teacher report on the Strengths and Difficulties Questionnaire, and grade point average (GPA) to indicate moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The needs of students with ever-increasing social, emotional, and behavioral health concerns continue to be unmet by many schools. This may be especially problematic in high school, as students with social, emotional, and behavioral concerns have difficulties balancing academic demands, peer relationships, and increased independence, while also facing greater opportunities to engage in risky behaviors (Margherio, Evans, & Owens, 2019 ). Without appropriate services, adolescents are at increased risk for negative outcomes in high school (e.g., truancy, failing classes, and suspension/expulsion; Mitchell, Kern, & Conroy, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needs of students with ever-increasing social, emotional, and behavioral health concerns continue to be unmet by many schools. This may be especially problematic in high school, as students with social, emotional, and behavioral concerns have difficulties balancing academic demands, peer relationships, and increased independence, while also facing greater opportunities to engage in risky behaviors (Margherio, Evans, & Owens, 2019 ). Without appropriate services, adolescents are at increased risk for negative outcomes in high school (e.g., truancy, failing classes, and suspension/expulsion; Mitchell, Kern, & Conroy, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the current study did not focus on creating cutoff scores for risk. Recently, researchers have noted the importance of systematically studying the implications of using cutoff scores within universal screening approaches (Margherio et al, 2019 ). Currently, the EIS-SR allows school personnel to identify individual students at the highest levels of risk based on school-normed data.…”
Section: Discussionmentioning
confidence: 99%
“…Others understood mental health to be related to both externalizing and internalizing behaviors and recognized the need to ensure students with internalizing behaviors do not “fall through the cracks” (Participant T‐SPED3). Indeed, a concern with universal screening has emerged in that universal screening assessment methods may not accurately capture and identify students with internalizing behaviors (Margherio et al, 2019).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Large class sizes have also been linked to teacher burnout (Caringi et al, 2015), and when coupled with CF as discussed earlier, this should be an area of consideration for addressing student mental health. Putting this concern within the context of an MTSS framework, the application of a universal screening procedure would help to identify students in need of support (McIntosh & Goodman, 2016), with an eye toward ensuring those with internalizing concerns are identified as well (Margherio et al, 2019).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…On the other hand, evidence from research on SEMS assessment using Likert-type questionnaires has shown that teachers' reports are a valuable source of information of students' social-emotional characteristics across time (Measelle et al, 2005;Wienke Totura et al, 2009;Edmonds et al, 2013;Margherio et al, 2019). Results from a longitudinal study of Measelle et al (2005), for example, indicated that teachers and parents' scores of children's Extraversion, Agreeableness, and Conscientiousness increasingly but moderately converged from ages 5 to 7.…”
Section: Accuracy In Reporting Sems Using Rubricsmentioning
confidence: 99%